Механізм підвищення зносостійкості сталі 110Г13Л модифікуванням, дисперсійним і дисперсним нітридним зміцненням - Шипицин, С.Я.; Федоров, Г.Є.; Карпець, М.В.; Локтіонов-Ремізовський, В.А.; Кірчу, І.Ф.; Лиховей, Д.І.; Степанова, Т.В. (Physico-technological Institute of Metals and Alloys, 2024)
The current state of industrial production of wear-resistant cast parts from high-manganese steels using various alloying, micro-alloying and modification technologies is analyzed in order to increase wear resistance not only in conditions of shock-abrasive, but also in conditions of purely abrasive wear. It is shown that despite the large number of technologies for the production of wear-resistant parts from these steels, there are no simple and highly effective methods. Prospective directions are dispersion hardening of metal by modification and microalloying of steels, in particular with nitrogen and vanadium, dispersion hardening by alloying of steels with titanium, niobium, etc. and the use of optimal modes of heat treatment. For the conditions of intensive shock-abrasive wear, it is important to establish the regularities of the influence of the degree of shock deformation on the formation of the surface martensitic layer in products after microalloying and modification of steels with nitrogen, dispersion and dispersion nitride hardening of the metal. It has been shown that dispersion nitride strengthening of metal by modifying steel with nitrogen or joint addition of nitrogen and vanadium to it and dispersion strengthening of metal after simultaneous addition of nitrogen, titanium and niobium significantly disperse the austenite grain of steel both in the cast state and after quenching. The change in the structure of steels due to the strengthening of the metal significantly affects their mechanical properties after various modes of heat treatment. Dispersive vanadium nitride strengthening increases strength by 15...17 % and plasticity by 45...50 %, and dispersed nitride strengthening increases plasticity by 45...60 % while maintaining the level of strength and slightly reducing impact toughness. The influence of the degree of impact deformation on the formation of e and a-martensite is shown, and a clear relationship between the increase in the degree of impact deformation and the increase in the amount of a-phase in the deformed layer is established. Impact deformation of about 16.6 % increases the amount of a-martensite in the deformed layer from 40 % to 98 %, which ensures an increase in the hardness of the deformed layer from 24 HRC to 36 HRC. It was noted that nitrogen modification, dispersion nitride and impact hardening of high-manganese steels increase their wear resistance by 1.5...2.0 times under conditions of dry sliding friction and 1.7...2.0 times under conditions of abrasive wear using unfixed and fixed abrasive.